2022
DOI: 10.3389/fcell.2022.841646
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on NF-κB Functions in Cellular Organelles

Abstract: NF-κB is diffusely recognized as a transcriptional factor able to modulate the expression of various genes involved in a broad spectrum of cellular functions, including proliferation, survival and migration. NF-κB is, however, also acting outside the nucleus and beyond its ability to binds to DNA. NF-κB is indeed found to localize inside different cellular organelles, such as mitochondria, endoplasmic reticulum, Golgi and nucleoli, where it acts through different partners in mediating various biological functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Subsequently, this mature NF-κB2 p52 relocates into the nucleus in conjunction with ReIB. A crucial player in orchestrating this degradation process is a signaling molecule called NF-κB-inducing kinase (NIK) ( 66 , 67 ). NIK effectively instigates the activation of IKKα and works in collaboration with it to facilitate the phosphorylation of p100 ( 34 , 68 ).…”
Section: Nuclear Factor Kappa B (Nf-κb): a Pioneer Shaping The Landsc...mentioning
confidence: 99%
“…Subsequently, this mature NF-κB2 p52 relocates into the nucleus in conjunction with ReIB. A crucial player in orchestrating this degradation process is a signaling molecule called NF-κB-inducing kinase (NIK) ( 66 , 67 ). NIK effectively instigates the activation of IKKα and works in collaboration with it to facilitate the phosphorylation of p100 ( 34 , 68 ).…”
Section: Nuclear Factor Kappa B (Nf-κb): a Pioneer Shaping The Landsc...mentioning
confidence: 99%
“…NF-κB has a dual role in the regulation of apoptosis, which is dependent on the balance between genes that controls cell survival and apoptosis. 257 In cancer cells, NF-κB activity interacts with various apoptotic and survival proteins. NF-κB can regulate PTEN through transcriptionally activate Snail, a repressor of PTEN, and thus regulate cell survival.…”
Section: Nf-κb Signaling In Human Diseasesmentioning
confidence: 99%
“…Certain extracellular mediators and cytokines may mediate the synergistic crosstalk between nuclear and mitochondrial gene expression. 55 Research has shown that the import of Signal transducer and activator of transcription 3 (STAT3) into mitochondria requires partner coordination and posttranslational modifications of STAT3, such as Ser727 phosphorylation and K87 acetylation. 56 Similarly, the RelA/IκBα complex also requires partner coordination to enter mitochondria.…”
Section: Rela and Stat3mentioning
confidence: 99%
“…NF‐κB participates in the regulation of classical nuclear genes and also plays a role in mitochondrial gene expression. Certain extracellular mediators and cytokines may mediate the synergistic cross‐talk between nuclear and mitochondrial gene expression 55 . Research has shown that the import of Signal transducer and activator of transcription 3 (STAT3) into mitochondria requires partner coordination and posttranslational modifications of STAT3, such as Ser727 phosphorylation and K87 acetylation 56 .…”
Section: Biological Role Of Nf‐κb Family In Mitochondriamentioning
confidence: 99%